Common spine codes are reimbursed 13% less by Medicaid compared to Medicare, ranging from 46% to 160% by state - Adam P. Henderson, BS; M. Lane Moore, MD, MBA; Camryn S. Payne, BA; Jack M. Haglin, MD, MS; Joseph C. Brinkman, MD; Paul R. Van Schuyver, MD; Joshua S. Bingham, MD; Michael S. Chang, MD (North American Spine Society Journal)
Background: Medicare reimbursement for spine procedures has been decreasing, and it is well-established that Medicaid reimburses physicians even less than Medicare. This study seeks to provide an updated analysis of Medicaid reimbursement using 24 common spine procedure codes. Methods: Medicaid rates were obtained from state online fee schedules, and Medicare rates from the Centers for Medicare and Medicaid online fee database. Rates were compared directly to each other by state and averaged to reflect national differences. The Medicare Wage Index was used to control for variability in wages between states and was used to adjust Medicaid data for comparison. Variability between states and codes was quantified using coefficient of variation values. Results: Medicaid reimbursement was lower than Medicare for all 24 included Current Procedural Terminology codes. Nationally, Medicaid rates were 13% less than Medicare, and this difference increased to 25% when adjusting for wage differences. Average cost differences were −$118 per code. Substantial variability between states and codes was also found for Medicaid, while little variability in Medicare rates existed. Conclusions: We found that Medicaid reimbursement to surgeons for 24 common spine surgeons was 13% less than Medicare on average. This difference increased to 25% when adjusting for wage differences. For Medicaid, wide variability existed between states and between different codes, indicating that some state payment systems may lack objective metrics when determining rates.